Influence of CYP3A5 and ABCB1 polymorphisms on the pharmacokinetics of vincristine in adult patients receiving CHOP therapy - Nakagawa, Junichi; Takahata, Takenori; Chen, Yu; Saito, Kensuke; Kamata, Kosuke; Tachita, Takuto; Yamashita, Satoru; Saito, Keigo; Ueno, Kayo; Sato, Atsushi; Sakuraba, Hirotake; Niioka, Takenori (Cancer chemotherapy and pharmacology, 2023)
Purpose This study aims to clarify the impact of CYP3A5 and ABCB1 polymorphisms on the pharmacokinetics of vincristine (VCR) in adult patients receiving CHOP therapy. Methods Plasma samples were collected immediately after the end of VCR administration and at 1.5, 2.5, 3.5, 5.5, 9.5, 13.5, and 25.5 h after the start of administration. Areas under the plasma concentration–time curves of VCR in the elimination phase (AUC 1.5–25.5 ) were calculated using the linear trapezoidal rule. Half-lives of VCR during the early phase (1.5–5.5 h) and terminal phase (5.5–25.5 h; t 1/2γ ) were determined according to the log-linear regression of the concentration–time data for at least 3 sampling points. Results A total of 41 adult patients were enrolled in this study. The median t 1/2γ and AUC 1.5–25.5 were significantly longer and higher in CYP3A5 non-expressers ( CYP3A5*3 / *3 ) than in CYP3A5 expressers ( CYP3A5*1 / *1 or *1 / *3 ) (21.3 vs 13.8 h, P = 0.005 and 35.5 vs 30.0 ng･h/mL, P = 0.006, respectively). Conversely, there were no significant differences in pharmacokinetic parameters among the ABCB1 c.1236C>T, c.2677G>A/T, c.3435C>T genotype groups. A stepwise selection multiple linear regression analysis showed that the dose of VCR administered and CYP3A5 non-expresser status were independent factors influencing the AUC 1.5–25.5 (partial R 2 = 0.212, P = 0.002 and partial R 2 = 0.143, P = 0.010, respectively). Conclusion The CYP3A5*3 polymorphism was found to be an indicator for predicting exposure to VCR in adult patients receiving CHOP therapy. This information may be useful for the individualization of VCR dosages.